Interpersonal Communication of Dating Apps Users in Digitized Relationships Among Urban Communities - Ade Firmannandya (Metafora: Education, Social Sciences and Humanities Journal, 2024)
Technological advancements connect people across the globe without distance or time constraints. However, this change also presents challenges in terms of face-to-face interaction, as well as dependence on the use of smartphones. The arrival of technology and internet developers of social media dating apps helps users to be able to communicate with strangers and build more intense interpersonal communication. The purpose of this study is to determine the dynamics or phenomenon of interpersonal communication in digital relationships among users of dating apps. The method in this study uses a literature review that is aligned with the topics discussed. The findings in this study are, but in its success, there is a tendency to show negative things and not sustainable to a more severe level. Dating app users use this application as a means of entertainment or to help introverts build social interactions. There is dissatisfaction between couples. So, further research is needed related to interpersonal communication strategies so that users of both couples on dating apps can be more intense and continue to the level of marriage.